Curriculum Standards Development of the Implemented CBI Model in the Context of UIN Suska Riau - Hasibuan, Kalayo (State Islamic University of Sultan Syarif Kasim Riau, 2018)
Content-based Instruction (CBI) has three most commonly known models. This article presents a Theme-based as one of the CBI models that has been implemented in integrating content and language for teaching students in higher education. The implemented model needs to be developed to keep up with new challenges and to be aligned with the curriculum standards and the students’ needs. Therefore, curriculum standards development is described to show the matrix of curriculum targets from personal or general-related goals to academic or work-related goals. Then, as the consequence of the curriculum standards development, a high possibility to implement two other types of CBI, namely the Sheltered Model and the Adjunct Model is also described.